Fibrinolytic and Renin Activity in Renal Vein Blood of Patients with Renovascular Hypertension - Nowak, A; Kokot, F; Czekała, Z; Dosiak, J; Kuska, J (Thrombosis and Haemostasis, 1969)
The fibrinolytic system has been studied in 20 patients with renovascular hypertension.Renal and hepatic venous blood was drawn by selective cathetherisations, while peripheral blood was obtained from the inferior vena cava above the bifurcation. In all blood samples the euglobulin fibrinolysis, antiplasmin, plasminogen, fibrinogen, and plasma renin activity were determined.Samples were taken at recumbency and after tilting to 80° for 30 min. In contradistinction to plasma renin activity no differences of the fibrinolytic activity between renal and peripheral venous blood even in that obtained from ischemic kidneys were proved.No diminished secretion of plasminogen activator by ischemic kidneys in man was stated.In the light of the data obtained the participation of fibrinolytic system in the pathogenesis of renovascular hypertension is doubtfal.